Application of Double Strength Reduction Factor Method in the Stability Analysis of Rock Slopes. (9th August 2021) - Lu, Jiawei; Zhang, Jixun; Ren, Xuhua; Deng, Yunrui
Abstract : The cohesion c and internal friction angle φ play different roles in the progressive failure process of the slope, which indicates that the reduction factors k c and k φ should be different in the calculation. Based on this, the program of double strength reduction factor method was compiled with FISH language, in order to study its application in the rock slopes under different distributions of weak interlayer, and the following conclusions were drawn: (1) the plastic zone calculated by double strength reduction factor method is generally distributed in the weak interlayer, which is basically consistent with the calculation result of the traditional method; (2) the degree to which c and φ play a role is related to the inclination angle of the bottom sliding surface of the unstable block θ . If θ  < 45°, φ will play a greater role. If θ  ≥ 45°, c will play a greater role; (3) according to the "Pan's principle, " the matching reduction principle of " k c  >  k φ " can be adopted when θ  < 45°, and the matching reduction principle of " k c  <  k φ " can be adopted when θ  ≥ 45°; (4) the definition of the comprehensive safety factor " K 2 " in the text is more suitable for the application of double strength reduction factor method in the stability analysis of rock slopes. The applicability of the above conclusions is verified by an actual engineering.